Solid state circuit breaker in DC network - Ho, Darren Zhan Rong (Nanyang Technological University, 2024)
DC Microgrids are becoming more popular in the power industry, and renewable energy is leading the way. However, every power system requires a protection system to guard against overloads and short circuits. Electrical circuit breakers play a crucial role in ensuring safety and dependability. But traditional mechanical circuit breakers have some drawbacks, including slow response times, short lifespans, and susceptibility to mechanical wear and tear. To overcome these issues, Solid State Circuit Breakers (SSCBs) that use semiconductor technology are a viable alternative. To address this problem, we will research and develop Solid-State Circuit breakers. These breakers are built using semiconductor switches, which have a faster breaking response time and longer lifespan compared to traditional mechanical circuit breakers. They also offer silent breaking technology since there are no moving parts in the system. Our project will aim to simulate the SSCB topology to identify a simple and efficient circuit. We will then build and test the system on a scaled-down version to demonstrate its feasibility and performance advantages over conventional mechanical circuit breakers. Through experimentation and analysis, we aim to prove the effectiveness of SSCBs in terms of response time, reliability, and scalability.